Successful Control of a Norovirus Outbreak in a Chilean Pediatric Intensive Care Unit. (October 2020) - Benadof, Dona; Garcia, Vanessa; Cifuentes, Paulina; Gaggero, Aldo
Abstract : Background: Noroviruses are nonenveloped, single-stranded RNA viruses belonging to the Caliciviridae family; they cause high-profile outbreaks in healthcare settings, due to their contagiousness, prolonged viral shedding, and ability to survive in the environment. Methods: Description of a norovirus outbreak in a pediatric ICU with multibed rooms. We report the epidemiology, molecular diagnosis, and control. Results: In August and September 2019, an outbreak of acute gastroenteritis affected 13 patients and 26 healthcare workers at an intensive care unit of Roberto Del Río Children's Hospital, which consists of 22 beds in a multibed-room format. Patients manifested self-limited nondysenteric diarrhea; other symptoms were vomiting (54%) and fever (23%). Healthcare workers reported diarrhea, nausea, vomiting, fever, malaise, and abdominal cramps. The mean age of the patients was 1 year old, all diaper users. The average days of diarrhea in patients was 4 days (2–6 days). There were 87 exposed patients, with an attack rate of 14.9% and 107 exposed staff, with an attack rate of 24.3%. Rotavirus and bacterial etiology were ruled out, and norovirus was subsequently diagnosed in 10 of 13 patients using qRT-PCR; 80% (8 of 10) corresponded with GII norovirus and 20% with a GI (2 of 10). Control measures included enforcement of standard precautions, strict adherence to contact precautions (use of gloves and gowns), hand hygiene before and after patients contact, and mask use if exposure to vomitus. Healthy staff were assigned for patients care. Environmental disinfection twice daily with 1.000 ppm sodium hypochlorite solution was encouraged and supervised with focus on cleaning high-touch surfaces, such as bathrooms, sinks, tables, floors and patient-care items. Active and prospective surveillance were conducted to search for new cases. Infection control practices were coupled with education to staff, patients, and visitors. The outbreak was controlled on September 18, 2019, after 23 days and several interventions, with complete recovery in all cases. Conclusions: We concluded that timely detection of a norovirus outbreak in a healthcare facility is imperative for effective infection control, especially in a multibed-room setting, because of the extended viral shedding in children and the transmission route that included aerosolized viral particles in vomitus. Molecular methods offer a rapid and definitive way to establish etiology, but these tests may not be accessible. Direct contact with infected children and contaminated surfaces and patient-care items were relevant risk factors in this outbreak (which involved both patients and healthcare workers) and contributed with its length. Funding: None Disclosures: None